2021
DOI: 10.13075/ijomeh.1896.01804
|View full text |Cite
|
Sign up to set email alerts
|

Acute SARS-CoV-2 infection and seropositivity among healthcare workers and medical students in summer 2020, Hungary

Abstract: The aim was to compare the prevalence of acute infection and seropositivity of SARS-CoV-2 among healthcare workers (HCWs) and medical students. Material and Methods: A high-volume, single-center analysis was conducted in the period of July 1-August 1, 2020, at the Semmelweis University. Naso-and oropharyngeal samples were collected for polymerase chain reaction (PCR), and blood samples for anti-SARS-CoV-2 IgG. A questionnaire was also administered about the infection symptoms and the obtained results were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…A similar age distribution was mentioned by Wouambo RK et al [6]. The gender distribution showed female prevalence (150/200; 75%, p < 0.0005) and was consistent with data from other studies [7][8][9]. Multiple studies have shown that females were more sensitive to eventual adverse health consequences of the pandemic, and therefore, they are more likely to comply with preventive measures, including testing for SARS-CoV-2 [10].…”
Section: Discussionsupporting
confidence: 86%
“…A similar age distribution was mentioned by Wouambo RK et al [6]. The gender distribution showed female prevalence (150/200; 75%, p < 0.0005) and was consistent with data from other studies [7][8][9]. Multiple studies have shown that females were more sensitive to eventual adverse health consequences of the pandemic, and therefore, they are more likely to comply with preventive measures, including testing for SARS-CoV-2 [10].…”
Section: Discussionsupporting
confidence: 86%
“…A study from Croatia found a 2.7% prevalence rate of SARS-CoV-2 antibodies after the first wave of the pandemic [ 11 ]. A high-volume, single-center Hungarian study, including physicians, other HCW and medical students confirmed 1.5%, 1.8% and 0.6% sero-prevalence rate during summer 2020 [ 12 ]. Three sero-epidemiological studies from eastern countries of the EU were conducted among specialist groups of HCWs (2 studies of HCWs in pediatric wards and 1 study of HCWs in gastroenterology units) [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,5 % [9,10]. Unterschiede in der Seroprävalenz zu Medizinstudierenden anderer Länder (Sa lamanca/Spanien 7-10 % im Oktober 2020 [6]; Budapest/Ungarn 0,6-2,1 % im Juli/August 2020 [7]), lassen sich am ehesten auf die damaligen lokalen COVID19Inzidenzen zurückführen.…”
Section: Diskussionunclassified
“…Zum SARS-CoV-2-Serostatus von Medizinstudierenden gibt es auch international bislang nur wenige veröffentlichte Daten 6 7 . Ziel der im Jahr 2020 begonnenen Studie war, die Seroprävalenz von Medizinstudierenden in der Anfangsphase der Pandemie zu ermitteln und mögliche Risikofaktoren für SARS-CoV-2-Exposition zu erfassen, um gegebenenfalls zeitnah Konsequenzen hinsichtlich ihrer Schulung zur Umsetzung von Infektionsschutz- und Hygienemaßnahmen ziehen zu können und damit zu einem besseren Schutz der Medizinstudierenden selbst und der von ihnen mitbetreuten Patienten beizutragen.…”
Section: Introductionunclassified
See 1 more Smart Citation